Analysis of E-Service Quality and Customer Satisfaction on Banking Image: A Survey of Bank XYZ Customers - Agung Mohamad Hikmah; Nunung Ayu Sofiati; Mochammad Mukti Ali; Yoyo Sudaryo; Ade Salman Alfarisi; Irving Ignatius Paul Luntungan; Riyandi Nur Sumawidjaya (Dinasti Publisher, 2025)
Sharia banks are financial institutions that conduct business activities based on Islamic sharia principles, such as fairness, transparency, and prohibition of riba (interest), gharar (uncertainty), and maisir (speculation). Unlike conventional banks, Islamic banks do not apply an interest system but instead use profit-sharing, buying and selling, and leasing schemes in accordance with the provisions of fiqh muamalah. This study aims to determine the effect of E-Service Quality on Customer Satisfaction and its impact on Banking Image at Bank XYZ. This study uses a quantitative method with descriptive and verificative approaches. Data analysis techniques use Structural Equation Modeling (SEM) with the Maximum Likelihood estimation method using the SPSS LISREL 8.80 program. The results of the study indicate that E-Service Quality, Customer Satisfaction, and Image have been implemented effectively. E-Service Quality has a significant impact on Customer Satisfaction at Bank XYZ, accounting for 62.4%. E-Service Quality has an impact on Banking Image at Bank XYZ, accounting for 6.4%. Customer Satisfaction influences Banking Image at Bank XYZ by 48.1%. E-Service Quality significantly influences Customer Satisfaction, which in turn affects Banking Image at Bank XYZ with a simultaneous influence of 82.1%.